Nonsense-mediated mRNA decay (NMD): a bifunctional mechanism in human physiology and disease - Fernandes, Rafael (2021)
Publication: Fernandes R, Nogueira G, da Costa PJ, Pinto F, Romão L. Nonsense-Mediated mRNA Decay in Development, Stress and Cancer. Adv Exp Med Biol. 2019;1157:41-83. doi: 10.1007/978-3-030-19966-1_3